PENERAPAN KALKULATOR GIZI DAN STANTING DI POSYANDU LESTARI 10 KELURAHAN BANTARSOKA - Tyas Pratama Puja Kusuma (Universitas Majalengka, 2023)
Posyandu Lestari 10 Bantarsoka sub-district is one of the posyandu that routinely carries out health control activities for children under five. There are 40 toddlers who regularly participate in posyandu activities at Posyandu Lestari 10. With so many toddlers participating in activities, it is not uncommon for posyandu cadres to feel overwhelmed in serving. To make it easier for posyandu cadres to determine the health of toddlers, a solution for making nutritional and stunting calculators emerged that can be used to calculate the growth and development of toddlers. With this calculator, cadres can easily calculate whether toddlers are in good or bad nutrition. The method used in the implementation of this Community Partner Amikom Service activity is to provide socialization and training. From the results of the analysis listed on the nutrition calculator and posyandu cadres, they can immediately find out whether the child is in good nutrition or not. Thus, the time needed for posyandu activities can be shorter and cadres no longer need to look at the graph tables of child growth in the Maternal and Child Health book, which cadres often do not read carefully. With the nutritional calculator and stunting can minimize errors in determining the health of toddlers. Keywords: Posyandu, Toddler, Nutrition, Stunting.